Female frog auditory sensitivity, male calls, and background noise: potential influences on the evolution of a peculiar matched filter. (24th October 2013) - Moreno‐Gómez, Felipe N.; Sueur, Jérôme; Soto‐Gamboa, Mauricio; Penna, Mario
<x xml:space="preserve">Abstract</x> The matched filter hypothesis proposes that the tuning of females' auditory sensitivity matches the spectral energy distribution of males' signals. Such correspondence is expected to arise over evolutionary time, as it promotes conspecific information transfer and reduces interference from other sound sources. Our main objective was to determine the correspondence between the acoustic sensitivity of female frogs of Eupsophus roseus and the spectral characteristics of advertisement vocalizations produced by conspecific males. We also aimed to determine how auditory sensitivity is related to the characteristics of background noise. We analysed data on the auditory sensitivity of E. roseus females, and recordings of conspecific male vocalizations and of the acoustic environment during the breeding period of this species. Our results indicate a concordance between the auditory sensitivity of females and call spectra that would provide an appropriate detection of these signals. In addition, this matching is large relative to the correspondence between auditory sensitivity with the spectra of the abiotic and biotic background noise, with the last component being associated with calls of the related species Eupsophus vertebralis. This may be an adaptation of receivers confronting sound interference, which improves the capability of E. roseus to communicate sexually by means of acoustic signals. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 110, 814–827.